Admission plasma neutrophil gelatinase associated lipocalin (NGAL) predicts worsening renal function during hospitalization and post discharge outcome in patients with acute heart failure. (September 2014) - Palazzuoli, Alberto; Ruocco, Gaetano; Beltrami, Matteo; Franci, Beatrice; Pellegrini, Marco; Lucani, Barbara; Nuti, Ranuccio; Ronco, Claudio
Abstract Background: The role of neutrophil gelatinase-associated lipocalin (NGAL) has been described in chronic heart failure (HF), however less data are available in patients admitted for acute HF. Methods: We evaluated the role of NGAL in predicting in-hospital worsening renal function (WRF) and post-discharge follow-up during six months period in patients with acute HF. All patients were submitted to creatinine, estimated glomerular filtration rate (eGFR), blood urea nitrogen (BUN) and B-type natriuretic peptide (BNP) measurement during hospitalization and before discharge. Results: Patients with chronic kidney dysfunction (CKD) demonstrated higher NGAL respect to subject with preserved renal function (241 ± 218 and 130 ± 80 ng/ml; P = 0.0001). In subgroup that developed WRF during hospitalization, NGAL levels were significantly increased respect to patients without WRF (272 ± 205 versus 136 ± 127 ng/ml; P = 0.0001). A cut off of 134 ng/ml has been related to WRF with good sensibility and specificity (92% and 71% AUC 0.83; P = 0.001). Multivariable Cox regression analysis showed that cut-off of 134 ng/ml was the only marker related to death (HR: 1.75; 95% CI: 1.24–2.45; P < 0.001). Follow-up analysis confirmed that NGAL > 130 ng/ml was associated with adverse events during a six-month period. Conclusion: Admission NGAL measurement appears a sensible tool for in-hospital WRF prediction as well as an early marker for adverse outcome during post discharge vulnerable phase.